Rights education without rights? Rights workshops and undocumented immigrants in the U.S. Issue 1 (2nd January 2022) - Tipler, Kathleen; Gates, Alice B.
ABSTRACT: Do rights education workshops have value when rights are difficult or impossible to claim? Drawing on three years of ethnographic field work of rights workshops for undocumented workers in the U.S., this article answers that question in the affirmative. Because of their legal status, these workers rarely, if ever, claimed rights. Yet for our subjects, these rights workshops played an important role. During in-depth interviews, attendees of the workshops described how they frequently experienced the law as an unpredictable and isolating force, which we trace to both their precarious legal status as well as their position as immigrants. Participants explained how rights education workshops shaped their experience of the law, introducing 1) a sense of predictability and control, alleviating fear and anxiety, 2) social support, reducing isolation and stigma, and 3) a sense of dignity and empowerment. We suggest that a right consciousness incorporating empowerment and dignity derives from rights' universalistic dimensions, while a rights consciousness culminating in mobilisation is dependent upon a group's status in local legal institutions.